5.3q-2.4-5.6=1.3q-3.1

Simple and best practice solution for 5.3q-2.4-5.6=1.3q-3.1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5.3q-2.4-5.6=1.3q-3.1 equation:


Simplifying
5.3q + -2.4 + -5.6 = 1.3q + -3.1

Reorder the terms:
-2.4 + -5.6 + 5.3q = 1.3q + -3.1

Combine like terms: -2.4 + -5.6 = -8
-8 + 5.3q = 1.3q + -3.1

Reorder the terms:
-8 + 5.3q = -3.1 + 1.3q

Solving
-8 + 5.3q = -3.1 + 1.3q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-1.3q' to each side of the equation.
-8 + 5.3q + -1.3q = -3.1 + 1.3q + -1.3q

Combine like terms: 5.3q + -1.3q = 4q
-8 + 4q = -3.1 + 1.3q + -1.3q

Combine like terms: 1.3q + -1.3q = 0.0
-8 + 4q = -3.1 + 0.0
-8 + 4q = -3.1

Add '8' to each side of the equation.
-8 + 8 + 4q = -3.1 + 8

Combine like terms: -8 + 8 = 0
0 + 4q = -3.1 + 8
4q = -3.1 + 8

Combine like terms: -3.1 + 8 = 4.9
4q = 4.9

Divide each side by '4'.
q = 1.225

Simplifying
q = 1.225

See similar equations:

| 14k^2-83km+33m^2=0 | | -16=x/y+2 | | 6(1+3z)=23.5 | | -4u-9=7 | | x^2-13x-59=0 | | 11(t-3)+3t=7(2t+4)-13 | | 24g^2+50gh+21h^2=0 | | 12*10-(13-7)/3-(7-6)= | | x^2-13x+59=0 | | 10c^2+99cd-10d^2=0 | | 1/4(x^2-3x+4)=0 | | 1/6(10x-2)=8 | | 1/4(x^2-3x+4) | | 35+4=3x | | 9u+7= | | -22-9a+8b-16-b-5a= | | .8y+4(2+y)=3(y-6)+10y | | 90-20*3+54/9= | | x-3/5=11/2 | | 1/5x-1/6(x-4)=6x | | 2/3x-1/3x=-4 | | 2/3x-1/3=-4 | | -24.5-5k=-9.5(6k+5.5) | | 22.5=-2(5n-6.5) | | 3/13x=12 | | 8n^2-9np-14p^2=0 | | [2x-1]=5 | | x-8.2=-5.8 | | x^2-7x=7-x | | 2x^2+16x=96 | | x^4+16=8x^2 | | 17m+6+13m+42= |

Equations solver categories